Control of the Nanoparticles Content in Cosmetic Medicines - Marina Viktorivna Rakhimova; Igor Nikolaevich Bondarenko; Oleg Grigorovitsh Avrunin; Andrii I. Fedosov; Irina A. Sych; Vitaliy Dmitrievich Yaremenko; Olha O. Vislous; Lina O. Perekhoda (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The safety of nanoparticles used in medical cosmetology and dermatology raises significant concerns. One of the tasks of analyzing the concentration of nanoparticles that must be solved for the practical analysis of the quality of products with nanoparticles is the quantitative analysis of the content of nanoparticles. The previously developed acousto-magnetic method (AMM) for determining the concentration of APIs as magnetic nanoparticles can be used to determine the nanoparticles' concentration when samples are prepared as a colloidal solution. It is shown that the described method not only can be applied for quality control in cosmetology and dermatology but also can be simplified by using a less sensitive magnetometer, which makes this direct method more available in the entire range of values ​​of the concentration of magnetic nanoparticles used in medical cosmetology and dermatology.